(3GSJQGJjLjI GdeDSSI (B: s (3eWHhYI ehLgI dWdHI GdSfI GdKGdKI GbJUGO h JSjjQ GdeDSSI (B/ s - (3HhJQjI, hgjHI s; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2022)
(3eONd Gdi GdGSJQGJjLjI h JWhQ GdacQ GdGSJQGJjLj (B((3eOGQS GdGSJQGJjLjI(B) (3, GdeDSSI h YdGbJgG HGdeMjW , GdGJMGg GdGSJQGJjLj (B((3GdJhLg GdGSJQGJjLj(B) (3, GdJLRFI GdGSJQGJjLjI , GdJTNjU GdGSJQGJjLj GdHjFI GdNGQLjI GdNGUI , JTNjU GdHjFI GdOGNdjI h JTNjU GdNGQLj h GdOGNdj eYG (B(SWOT) (3, eUahaGJ GdhVYjI GdJfGaSjI , GdHOGFd GdGSJQGJjLjI (B((3GdNjGQGJ GdGSJQGJjLjI(B) (3h GdJfajP GdGSJQGJjLj h GdQbGHI GdGSjJQGJjLjI , GSJQGJjLjI GdeMjW GdCRQb (B.s
(3eQGLY U(B.100s
Keywords: (3GSJQGJjLjI GdeDSSGJs; (3GdGSJQGJjLjIs